Analysis of tribological efficiency of movable junctions "polymericcomposite materials ‒ steel" - Aulin, Viktor; Derkach, Oleksii; Makarenko, Dmytro; Hrynkiv, Andrii; Pankov, Andrii; Tykhyi, Andrii (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports an analysis into tribological efficiency of mating parts "polymeric-composite materials ‒ steel" is carried out. Improperly selected materials produce significant operating costs in terms of tribology. Therefore, selecting the type of polymeric-composite materials to be used in the structures of nodes and machine parts is a task related to substantial improvement of their technical level. The testing of samples made from polymeric-composite materials for relative abrasive resistance when mated with samples made from steel 45 has made it possible to establish that the lowest value for weight wear was demonstrated by material Nylon 66. Among the examined materials, the closest to Nylon 66 in terms of the values for relative abrasive resistance is the material PA-6-210KS that demonstrated the values that are 1.65 times less. During operation of machines, in the presence of abrasive wear, it is advisable to mate the materials "Nylon 66 – steel 45" and "PA-6-210KS – steel 45". The results from a tribotechnical study without lubrication at the friction machine SMC-2 for the mating parts "polymeric-composite material – steel 45" make it possible to establish that the least wear was demonstrated by sample made from the material UPA-6-30, that is 0.00083 g. In terms of wear resistance, the closest to it is a sample from the material PAG/6.6 R196-GF30, which is 6.1 times greater for weight wear. The sample made from steel 45 mated with a sample from the material UPA-6-30 has the lowest value of weight wear, 0.00005 g. At the same time, the lowest value for the friction coefficient is demonstrated by the mated materials "steel 45 – UPA-6-30", 0.163. The progress of the mating process is achieved fastest, after 20 minutes, when using the material UPA-6-30 at a temperature in the friction zone of 348±2 K. Our research is necessary to substantiate further utilization and selection of polymeric-composite materials for mating parts working under difficult conditions. The current study is of interest to manufacturers of agricultural and quarry machinery and various transport machines.